"Covering Effects" under Diurnal Temperature Variations in Arid and Semiarid Areas. (21st February 2020) - Liu, Feifei; Mao, Xuesong; Xu, Cheng; Li, Yingying; Wu, Qian; Zhang, Jianxun
Abstract : "Covering effects" dominated by water vapor migration in arid and semiarid areas threaten the stability of engineering entities. To explore the "covering effects" dominated by water vapor migration under the influence of diurnal temperature variations, a series of one-side evaporation experiments were conducted. Characteristics of water vapor migration between the unsaturated loess soil column with and without a lid were compared in detail to illustrate the "covering effects" on water vapor migration, as were the effects of test time. Further, the characteristics of "covering effects" in loess and sand soil columns were compared. The results show that the "covering effects" formed in the loess soil column with a lid by cycling day and night temperature differences led water vapor to accumulate and condense beneath the lid. However, unlike the "covering effects" during freezing conditions that lead to a significant increase in the moisture content in the top layer, in this study, the moisture content in the top layer (0–8 cm) decreased. Although "soil lid" and the "soil covering effects" exist in both loess soil columns with and without lids, the "soil covering effects" for the former are much more obvious, and the moisture content in the upper part of the loess soil column (8–45 cm) shows a significant increase. By cycling day and night temperature differences, the "covering effects" or "soil covering effects" grew as the test time increased. Compared to the loess soil column, the "covering effects" in the sand soil column were extremely weak, and the moisture migration in the sand soil column was dominated by the downward movement liquid water. This paper illustrates the "covering effects" under the influence of diurnal temperature variations and reveals the mechanism of water vapor migration in subgrade soils in arid and semiarid areas.